KONFLIK TOKOH DALAM DRAMA LEONCE UND LENA KARYA GEORG BÃœCHNER - WULANDARI, WIDYA (UNIVERSITAS NEGERI SURABAYA, 2016)
According to Wellek and Waren (1995: 285), conflict is the essential incident of plot expansion in literature. Thus, conflict is important in the theatre because the fundamental conflict is human conflict. The research questions of this research are; (1) How does the conflicts happen between the characters in the theatre “Leonce und Lena” by Georg Büchner? (2) How do the factors affect the internal and external conflict happen between the characters in the theatre “Leonce und Lena” by Georg Büchner? The purpose of this research is to describe; (1) The conflict of characters, (2) The factors which affect the internal and external conflicts happen. The research design was used in this research is descriptive qualitative research. The theory which was used in this research Nurgiyantoro and Peg Pickering theory. The data analysis was done by (1) reading the research object deeply, (2) searching the data which contain conflicts and the factors, (3) analyzing the conflicts and the factors, and (4) describing the conflicts and the factors. Thus, the results of this research are, (1) there are internal and external conflicts which happen in the theatre script, (2) the factors which affect the internal conflict consists of a) the emotional affliction since the demand and hope unqualified, b) the experience, interest, purpose, or the self-value have a contradictory with others. Meanwhile, the factors which affect the external conflict consists of a) the desire to be appreciate and to be treated as human, b) desire to have self-respect, and d) desire to consistent Keywords : Conflict, Charakter, Leonce und Lena by Georg Büchner